(untitled) (Revista Sistemas de Producción Agroecológicos, 2025)
Aim was to conduct a systematic review on the original antigenic sin (OAS) phenomena in coronavirus 2019 patients who present antibodies or cross-reactivity T cells previously generated by endemic human coronaviruses (HCoV), as well as the implications on the humoral response, disease severity, and vaccination efficacy. This systematic review was structured following PRISMA protocol, the search was made in three databases: NCBI, BVS, and EMBASE following the next terms: Original antigenic sin, SARS-CoV-2, immunological memory, cross-reactivity, human coronavirus 229E, human coronavirus NL63, and human coronavirus OC43. 956 scientific papers were recovered through the searching strategy. Among them, 724 MEDLINE articles, 200 EMBASE articles, and 28 BVS articles. Then, the duplicates were removed, followed by the implementation of the inclusion and exclusion criteria. 60 articles that fit the systematic review were included. The immunological memory generated by endemic HCoV has the capacity to induce immunopathology through OAS, increasing immunoglobulins (Ig) class G or class titles describing cross-reactivity with non-neutralizing epitopes of Severe Acute Respiratory Syndrome coronavirus 2 and decreasing de novo antibodies response against neutralizing epitopes. The clinical picture can be worse thanks to antibody-dependent enhancement (ADE). Finally, there is no evidence that existing SARS-CoV-2 vaccines induce ADE or are influenced by OAS.